Effect of glucocorticoid on cytokines TLR9 and TLR7 in peripheral blood for patients with uveitis - Cui, Hong-Pei (Exp Ther Med, 2016)
The effect of glucocorticoid on cytokines Toll-like receptor (TLR)9 and TLR7 in peripheral blood of patients with uveitis was explored. Forty-six patients with uveitis admitted to our hospital from April 2014 to April 2015 were selected as the research observational group. Thirty-five able-bodied individuals in the same period were selected as the control group. To treat uveitis, the observational group was injected with glucocorticoid (1–2 mg/kg/day) daily, while the control group did not receive any treatment. The quantity of expression of peripheral blood cytokines TLR9 and TLR7 were detected by the methods of fluorescence quantitative PCR, enzyme-linked immunosorbent assay and western blotting. The content of peripheral blood TLR9 and TLR7 (0.21±0.01, 0.19±0.01) decreased significantly (P<0.05) in observational group after glucocorticoid treatment. Compared with data of control group (0.21±0.01, 0.19±0.01), TLR9 and TLR7 content in peripheral blood after glucocorticoid treatment on the patients with uveitis from observation group (0.19±0.01, 0.17±0.01) did not show any significant difference, for correlation between TLR9 and TLR7 in observation group before and after treatment. It was observed that the cytokine content of TLR9 was associated with TLR7 positively (r=0.653, P=0.012). In conclusion, glucocorticoid can improve uveitis by reducing the content of cytokines TLR9 and TLR7 in peripheral blood.